HNF1A-MODY Mutations in Nuclear Localization Signal Impair HNF1A-Import Receptor KPNA6 Interactions - Fareed, Fareed M. A.; Korulu, Sirin; Ozbil, Mehmet; Capan, Ozlem Yalcin (SPRINGER, 2021)
Mutations in hepatocyte nuclear factor (HNF)1A gene cause the most common form of Maturity-onset diabetes of the young (MODY), a monogenic subtype of diabetes mellitus. Functional characterization of mutant proteins reveals that mutations may disrupt DNA binding capacity, transactivation ability and nuclear localization of HNF1A depending on the position of the mutation. Previously identified Arg271Trp and Ser345Tyr mutations in HNF1A were found to be defective in nuclear localization. Arg271 residue resides in a region similar to classical nuclear localization signal (NLS) motif, while Ser345 does not. Importin alpha family members recognize NLS motifs on cargo proteins and subsequently translocate them into nucleus. Here, we first investigated the nuclear localization mechanism of wild type HNF1A protein. For this purpose, we analyzed the interaction of HNF1A with three mouse homolog importin alpha proteins (KPNA2, KPNA4 and KPNA6) by co-immunoprecipitation assay and molecular docking simulation. Hereby, KPNA6 was identified as the main import receptor, which is responsible for the transport of HNF1A into the nucleus. Immunolocalization studies in mouse pancreatic cells (Min6) also confirmed the co-localization of HNF1A and KPNA6 in the cytoplasm. Secondly, the interaction between KPNA6 and mutant HNF1A proteins (Arg271Trp and Ser345Tyr) was assessed. Co-immunoprecipitation studies revealed a reduced interaction compared to wild type HNF1A. Our study demonstrated for the first time that HNF1A transcription factor is recognized and transported by importin/karyopherin import family, and mutations in NLS motifs may disrupt the interaction leading to nuclear localization abnormalities and MODY phenotype.
Keywords: MODY; HNF1A; Nuclear localization signal; Nuclear import; Molecular docking; Biochemistry & Molecular Biology